2020
DOI: 10.1177/0004867420963740
|View full text |Cite
|
Sign up to set email alerts
|

The association between lithium in drinking water and neuropsychiatric outcomes: A systematic review and meta-analysis from across 2678 regions containing 113 million people

Abstract: Background: Lithium in drinking water may have significant mental health benefits. We investigated the evidence on the association between lithium concentrations in drinking water and their neuropsychiatric outcomes. Methods: We conducted a systematic review and meta-analysis and searched Pubmed, Embase, Web of Science, PsycINFO and CINAHL up to 19 January 2020, for peer-reviewed research examining the association between lithium concentrations in drinking water and neuropsychiatric outcomes. We used a pairwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…As expected, the lithium concentration in the aqueous humor reflected that in the serum and did not significantly change after death. This result is consistent with previous ecological studies showing an inverse correlation between regional lithium concentration in drinking water and suicide rate [15]. The findings of the present study also accord with those of a previous study, suggesting that the lithium concentration in the brain is lower in suicide than in a non-suicide victim [20].…”
Section: Discussionsupporting
confidence: 94%
“…As expected, the lithium concentration in the aqueous humor reflected that in the serum and did not significantly change after death. This result is consistent with previous ecological studies showing an inverse correlation between regional lithium concentration in drinking water and suicide rate [15]. The findings of the present study also accord with those of a previous study, suggesting that the lithium concentration in the brain is lower in suicide than in a non-suicide victim [20].…”
Section: Discussionsupporting
confidence: 94%
“…This challenges the results of previous meta-analyses of randomised trials (Cipriani et al ., 2013 ; Smith and Cipriani, 2017 ), guideline recommendations (Veterans Affairs and Department of Defence, (2019 ) and the longstanding consensus that lithium reduces the risk of suicide. It contrasts with ecological studies that find associations between lithium levels in drinking water and suicide rates, suggesting they may have been influenced by publication bias, which is evident in some reviews (Eyre-Watt et al ., 2021 ). In contrast, our results are consistent with a previous systematic review, although this only included a single trial (Borjesson and Gotzsche, 2019 ), with an earlier Cochrane review published in 2001, which included four trials in total, two of which were included in the meta-analysis (Burgess et al ., 2001 ), and with the fact that the largest trial of lithium for suicide prevention, published in 2021, was terminated early due to lack of effect (Katz et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…An influential meta-analysis of randomised trials also concluded that lithium can reduce the risk of suicide (Cipriani et al ., 2013 ). Moreover, ecological analyses have reported associations between lithium levels in drinking water and lower suicide rates (Memon et al ., 2020 ), although publication bias and heterogeneity are noted as limitations in the latest meta-analysis of these studies (Eyre-Watt et al ., 2021 ). Thus, despite some recent analyses coming to different conclusions (Riblet et al ., 2017 ; Borjesson and Gotzsche, 2019 ), many researchers and clinicians regard lithium's anti-suicidal properties as ‘proven’ (Lewitzka et al ., 2015a , p. 1) by ‘unambiguous evidence’ (Lewitzka et al ., 2015b , p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…This study can be considered as pioneering, since Li is found naturally in drinking water (Eyre-Watt et al, 2020;Ewuzie et al, 2020) with various origins. In clinical practice, it is widely used in the treatment of bipolar and of mood disorders.…”
Section: Anthropogenic Origin Of LI In the Egoutier Watershedmentioning
confidence: 99%